2017
DOI: 10.3390/rs9070650
|View full text |Cite
|
Sign up to set email alerts
|

Suitability Assessment of Satellite-Derived Drought Indices for Mongolian Grassland

Abstract: Abstract:In Mongolia, drought is a major natural disaster that can influence and devastate large regions, reduce livestock production, cause economic damage, and accelerate desertification in association with destructive human activities. The objective of this article is to determine the optimal satellite-derived drought indices for accurate and real-time expression of grassland drought in Mongolia. Firstly, an adaptability analysis was performed by comparing nine remote sensing-derived drought indices with re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(23 citation statements)
references
References 36 publications
2
20
0
1
Order By: Relevance
“…Nevertheless, to date, no studies of crop yield estimation using remote sensing indicators have been done yet in Mongolia. Recently, remote sensing indicators are employed to monitor the drought across the pasture lands of Mongolia [44] and provide valuable information for drought management and reduction. Compared to drought, more attention should be paid to crop yield, while these indices were not getting enough attention in the field of crop yield in Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, to date, no studies of crop yield estimation using remote sensing indicators have been done yet in Mongolia. Recently, remote sensing indicators are employed to monitor the drought across the pasture lands of Mongolia [44] and provide valuable information for drought management and reduction. Compared to drought, more attention should be paid to crop yield, while these indices were not getting enough attention in the field of crop yield in Mongolia.…”
Section: Introductionmentioning
confidence: 99%
“…Desertification is a serious global environmental problem. Under the influence of natural environmental change and the anthropogenic causes of grassland degradation, ecological and environmental deterioration, as well as desertification have become more severe in Mongolia [1]. Plant species from 1961 to 2006 in the forest steppe, real steppe, mountain steppe, desert steppe, and desert regions in Mongolia were reduced by 50.0%, 44.7%, 30.3%, 23.8%, and 26.7%, respectively [2].…”
Section: Introductionmentioning
confidence: 99%
“…The Vegetation Health Index (VHI) is a health condition index that takes into account the effect of vegetation leaf surface and temperature on vegetation. The VHI is used to reflect the differences in the spatio-temporal patterns of drought and has a better effect of drought monitoring [18]. Sandholt et al indicated that there was a triangular or trapezoidal relationship between the vegetation index and land surface temperature, and developed the Temperature Vegetation Dryness Index (TVDI) based on the scattered point feature space of these two parameters [19].…”
Section: Introductionmentioning
confidence: 99%